AB0844-HPR Dance class dedicated to scleroderma patients: joint evaluation, functional and quality of life before and after treatment – clinical trial. (23rd January 2014) - Schiavi, M.; Giuggioli, D.; Spinella, A.; Ferri, C.; Mascia, M. T.
Abstract : Background: Systemic sclerosis (SSc) is a complex and multi systemic disorder of connective tissue, characterized by progressive thickening and fibrosis of the skin and internal organs, as well as by widespread microvascular damage. A number of studies have described in these patients a high prevalence of depressive symptoms, pain, and body image dissatisfaction. Physical and occupational therapy showed to be useful in preserving mobility in patients with scleroderma but no specific study was found that investigated exactly what kind of activity could improve disability, encourage participation and improve mood. Objectives: Dance (as a work of stretching, coordination, strength, aerobic, rhythmic, and recreational activity) could lead not just to accept and reconnect the patients with their bodies, enhance self-expression, address feelings of isolation and depression, but also to improve joint width, functionality, and autonomy. The study aims to compare the effects of dance/movement therapy and standard care with standard care alone in patients with systemic sclerosis. Methods: 15 female patients diagnosed with SSc were divided into an experimental group -A-(5 patients enrolled spontaneously, considering that not all are willing to participate) and in a control group-C- (10 patients). The group A followed a dance routine devotedly for 4 months (1 hour twice a week). at T0 and after 4 months were evaluated: Subjective Functionality upper limb (QUICK DASH), Autonomy of daily living (SHAQ Scleroderma- Health Assessment Questionnaire), mood ( CES-D), Fatigue (FS Scale) Objective- Six Minutes Walking Test (6MWT), ROM of the shoulder and hip. In both groups, the changes in the outcome measures between the baseline and 16-week assessments were assessed with a paired t-test. Results: There has been a statistically significant improvement in the group A in the objective evaluation: joint ROM of flexion of the hip and shoulder, meters walked in 6MWT(p< 0.03), test Borg dyspnea before the 6MWT is reduced from 0.6 to 0 and after the 6MWT is reduced from 2 to 0.8, while in the control group both remain unchanged (from 0.8 to 1 and 2.1 to 2.2). The self-assessment questionnaires show in the dancer group an improvement in the perception of fatigue (p <0.02) and of mood (p <0.01). No improvement was recorded in HAQ (0.58 to 0.65) and in the functionality of the upper limb (Quick Dash) due to worsening in work items (from 21.9 to 46.2) and a marked improvement in the free time items (from 40.6 to 21.5) probably attributable to awareness of disease. The results of the objective and subjective tests at time 0 and after 4 months were unchanged in the control group. Conclusions: The results should be interpreted with caution given the small sample. However, it can be said that the experimental dance program has brought a gain in aerobic performance, perception of fatigue, mood as well as hip and shoulder joints flexibility. The patients indicated that they liked the course and continued to dance even at the end of the trial outside of the dance school References: – Maddali Bongi S (2006):Riabilitazione reumatologica. Approccio multidisciplinare. Milano, Edizioni EDRA – Poole JL. Musculoskeletal rehabilitation in the person with scleroderma. Curr Opin Rheumatol. 2010;22(2):205–12 Disclosure of Interest: None Declared